posted by .

1. Given f(x)=x^2 and g(x)=x+2, determine in standard form:
a) g(f(x))
b) when f(g(x))=g(f(x))

2. If f = {(-10, 1), (-1, -1), (10, 0), (11, 7)} and g = {(-1, -1), (0, 10), (1, -10), (7, 11)} for how many values of x is f x g defined? Explain

3. Given f(x) = -2x + 3 and g(x) = 3x + 4, x ε R, use the sketches of both functions to graph (fg)(x) on the same graph. Show your work.

#1.
g(f) = f+2 = x^2+2
f(g) = g^2 = (x+2)^2
so, when do we have

x^2+2 = (x+2)^2
?

#2.
f and g are both defined only on {-1}

#3.
visit wolframalpha.com
(fg)(x) = -6x^2+x+12

## Similar Questions

1. ### math/Check!

a. An ellipse is formed by stretching the graph of x^2+ y^2=1 horizontally by a factor of 3 and vertically by a factor of 4. Determine the equation of the ellipse in standard form x^2/a^2+y^2/b^2=1 (x/3) ^2+ (y/4) ^2=1 x^2/9 + y^2/16 …

Find an equation with the given form in each case below. y=sin through(Ï/2, 0)
3. ### Precalculus

Evaluate all six trigonometric functions at t, where the given point lies on the terminal side of an angle of t radians in standard position. (40/41, -9/41)

Evaluate all six trigonometric functions at t, where the given point lies on the terminal side of an angle of t radians in standard position. (40/41, -9/41)

Beginning with the function f(x) = (0.8)x, state what transformations were used on this to obtain the functions given below: g(x) = - (0.8)x -2 h(x) = ½ (0.8)x-2 k(x) = (0.8)-3x+9

1. Given f(x)=x^2 and g(x)=x+2, determine in standard form: a)g(f(x)) b)when f(g(x))=g(f(x)) for #1 would the answer for a be x^2+2?